FAMILY SARCOPHAGIDAE - de Mello-Patiu, Cátia Antunes (Zootaxa, 2016)
A catalogue of Sarcophagidae recorded from Colombia is presented, including 102 species in 26 genera, and two subfamilies. The geographical distribution by department is also given.